Metil Bromida (CH3Br) Sebagai Fumigan Hama Gudang Areca Nut Weevil (Araecerus fascicullatus De Geer) (Coleoptera : Anthribidae) Pada Biji Pinang - Nirza Okta Yudistira; Darma Bakti; Fatimah Zahara (Jurnal Agroekoteknologi, 2014)
This research aimed to know the apropriate concentration for controlling A. fasciculatus on severaldose and time exposure. This research was conducted in shading house of agriculture quarantinemain centre, Belawan Gedung Johor, ± 25 m above sea level, started on February to April 2014.This research used randomized complete design, with two factors and three the replicate, firts factorwas replication dose of Methyl Bromide (0 g/m3, 24 g/m3, 32g/m3and 40 g/m3) and second wastimeexposure ( 2 hours, 4 hours and 12 hours). The result showed that dose and time exposure of MethylBromide so significantly affected to mortality percentage, as well as interaction between twofactors. The best result showed on D3 (dose 40 g/m3) with mortality rate 85,16% and T3 (exposuretime 6 hours) with mortality rate 51,09%.Keywords :Fumigation, A. fascicullatus, Methyl Bromide, Areca nut